The crystal structure and photocatalytic properties of a three‐dimensional cadmium(II) metal–organic framework: poly[bis(μ3‐benzene‐1, 2‐dicarboxylato)[μ2‐1, 4‐bis(pyridin‐3‐ylmethoxy)benzene]dicadmium(II)]. Issue 3 (5th February 2016) - Yu, Cai-Xia; Gao, Yan-Ping; Cui, Xiao-Qing; Guo, Meng-Jiao; Liu, Lei-Lei
Abstract : A three‐dimensional cadmium(II) complex metal–organic framework incorporating benzene‐1, 2‐dicarboxylate and 1, 4‐bis(pyridin‐3‐ylmethoxy)benzene ligands possesses a threefold interpenetrating net. The compound exhibits relatively good photocatalytic activity towards the degradation of methylene blue in aqueous solution under UV irradiation. Abstract : Photocatalysis is a green technology for the treatment of all kinds of contaminants and has advantages over other treatment methods. Recently, much effort has been devoted to developing new photocatalytic materials based on metal–organic frameworks for use in the degradation of many kinds of organic contaminants. With the aim of searching for more effective photocatalysts, the title three‐dimensional coordination polymer, [Cd2 (C8 H4 O4 )2 (C18 H16 N2 O2 )] n, was prepared. The asymmetric unit contains one Cd II cation, one benzene‐1, 2‐dicarboxylate anion (denoted L 2− ) and half of a centrosymmetric 1, 4‐bis(pyridin‐3‐ylmethoxy)benzene ligand (denoted bpmb). Each Cd II centre is five‐coordinated by four carboxylate O atoms from two L 2− ligands and by one N atom from a bpmb ligand, forming a disordered pentagonal pyramidal coordination geometry. The Cd II centres are interlinked by L 2− ligands to form a one‐dimensional [Cd2 L 2 ] n chain. Adjacent chains are further connected by bpmb linkers, giving rise to a two‐dimensional network, and these networks are pillared by bpmb to afford a three‐dimensional framework with a 3 3 .4 2 .6 3 .7 1 .8 1 topology. Each grid in the framework has large channels which are filled mainly by the two other equivalent frameworks to form a threefold interpenetrating net. The compound exhibits relatively good photocatalytic activity towards the degradation of methylene blue in aqueous solution under UV irradiation.